1980
DOI: 10.1056/nejm198004103021503
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Suppressor Cells and Suppressor Factors in Human Filariasis withBrugia malayi

Abstract: We investigated the mechanisms of specific immune unresponsiveness to microfilarial antigens. The blood of patients with obvious Brugia malayi infections contains an adherent cell type that specifically suppresses reactions to microfilarial antigens but not to other antigens. In the absence of continued stimulation by parasite antigens, this suppressor cell loses its functional activity after overnight culture in vitro. Furthermore, serums from patients with and without microfilaremia contain factors that also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 8 publications
4
48
0
Order By: Relevance
“…illy (20), and as markedly reduced T lymphocyte proliferation responses to parasite antigens in vitro, but not to nonparasite antigens (4,9,10,21). The specific B cell deficits in these microfilaremic patients are reflected both in low serum levels of parasite-specific antibodies (3,6,22) and in impaired immunoglobulin production by PBMC in response to parasite antigens in vitro (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…illy (20), and as markedly reduced T lymphocyte proliferation responses to parasite antigens in vitro, but not to nonparasite antigens (4,9,10,21). The specific B cell deficits in these microfilaremic patients are reflected both in low serum levels of parasite-specific antibodies (3,6,22) and in impaired immunoglobulin production by PBMC in response to parasite antigens in vitro (7).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms underlying this parasite-specific immune hyporesponsiveness have been postulated to involve adherent suppressor cells (presumably monocytes), serum suppressive factors (9), or suppressor T lymphocytes (10). Alternatively, the immunologically hyporesponsive microfilaremic state may result from a diminished number of parasite antigen-responsive lymphocytes (7) as a consequence of perinatal sensitization or tolerization to the parasite.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, both down-regulation by IL-10 and/or TGF-␤ (4 -7), regulation by Th3 or Tr1 cells (3), and changes in the balance of type 1 and type 2 CD4 ϩ cells (4,8) have each been implicated as important mechanisms underlying the filaria-specific down-regulated state. Indeed, Ͼ2 decades ago it was demonstrated that patently infected (microfilaria-positive (Mf ϩ ) 2 ) patients had demonstrable Ag-specific suppressor T cells (9) as well as non-T cell-derived suppressor factors (10). More recently, it has been shown that most, but not all, (11) of this modulating activity is a consequence of the interaction between the microfilarial stage of the parasite (12) and the host cellular immune system, some of which may occur neonatally (13-18).…”
Section: Ctla-4 In Filarial Infectionsmentioning
confidence: 99%
“…Parasite prod-ucts that suppress in vitro lymphocyte responses to specific antigens have been described in chronic mucocutaneous candidiasis (12), schistosomiasis (1), leprosy (13), and tuberculosis (14). Moreover, autologouis seruim inhibits in vitro responses of lymphocytes from patients with schistosomiasis (15), histoplasmosis (16), filariasis (3), and tuberculosis (17). Our study of tuberculosis explored whether suppressive plasma factors, possibly mycoblacterial in origin, alter monocyte function, and thereby induce immunosuppression during the course of infection.…”
Section: Introductionmentioning
confidence: 99%